Literature Review on Cinematic Technique in Video Game Storytelling - Tony Wibowo; Deli Deli; Bayu Syahputra (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
Cinema and filmmaking have evolved over the years into a means of creatively telling a story. The combination of camera angle, movement, framing, and composition is used to convey narrative in so many variations. However, cinematic techniques have been used extensively in media other than film, and one of those media that has adopted the cinematic approach to conveying narrative, feeling, and story is video games. As video games have evolved in their narrative complexity and graphical realism, cinematic techniques have become increasingly common in video game storytelling. Narratologists argue that video games often mimic the look and experience of films by adopting similar cinematic techniques or introducing cut scenes, which are small digital films. This article aims to categorize and compare video game storytelling and its use of cinematic techniques across genres, generations, and platforms by examining relevant articles and recent updates from the video game industry. The use of cinematic storytelling in video games could respond to the evolving film industry to create a more immersive and interactive form of storytelling. Video game storytelling can also benefit from adopting cinematic techniques to increase player engagement and emotional connection with the game's narrative and immersion to world-building and mythos presented in the video games.